2002
DOI: 10.1046/j.1365-2427.2002.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity and food choice of piscivorous perch (Perca fluviatilis) in a eutrophic shallow lake: a radio‐telemetry study

Abstract: SUMMARY 1. Radio transmitters were implanted in large perch (27–37 cm) in a shallow lake in Denmark. Between 6 and 13 perch were tracked every 3 h for 24‐h periods twice (summer) or once a month (winter) from August 1997 to July 1998. Activity levels were recorded as minimum distance moved per hour. 2. No significant differences in activity levels of individual fish were observed. 3. Highest activities were observed at daytime with peaks at dawn and dusk or midday. This diel pattern was most pronounced from Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 30 publications
8
48
1
Order By: Relevance
“…It could be argued that the observed patterns are overestimated due to adverse effects of tagging making the tagged fish more prone to predation. However, studies have demonstrated that perch tagged with relatively larger tags than used in this study performed well (Baras et al, 2000;Jacobsen et al, 2002) and for most tagged fish, the tag/bodymass ratio was well below recommended threshold . In contrast we would argue that our results are in fact underestimating the real magnitude of the predation.…”
Section: Predation On Perch and Its Management Implicationsmentioning
confidence: 67%
“…It could be argued that the observed patterns are overestimated due to adverse effects of tagging making the tagged fish more prone to predation. However, studies have demonstrated that perch tagged with relatively larger tags than used in this study performed well (Baras et al, 2000;Jacobsen et al, 2002) and for most tagged fish, the tag/bodymass ratio was well below recommended threshold . In contrast we would argue that our results are in fact underestimating the real magnitude of the predation.…”
Section: Predation On Perch and Its Management Implicationsmentioning
confidence: 67%
“…While there have been numerous studies on fish predation by perch (e.g. Horppila et al, 2000;Specziár and Rezsu, 2009;Didenko and Gurbyk, 2016), with observations including cannibalism on perch fry (Lohnisky, 1960;Craig, 2000) and/or predation upon YOY planktivorous cyprinids (Jacobsen et al, 2002;, very few have recorded perch foraging on benthic and/ or shelter dwelling fish species such as gobies (see Almquist et al, 2010;Taraborelli et al, 2010). Further, while the consumption of gobiids by predatory fishes in general has been widely studied in North American waters (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Why perch inŘímov Reservoir restricted their spawning to shallow depths and why records of egg strands from water >3 m deep are so sporadic? Perch is a visually orientating fish (Ali et al, 1977;Jacobsen et al, 2002) and, as shown by Hergenrader (1969), perch spawning also takes place during daylight hours (most probably, visual communication plays an important role in perch spawning/courtship rituals). Visibility in the water column is therefore essential for spawning perch.…”
Section: Discussionmentioning
confidence: 99%
“…Perch is a visually orienting fish primarily active in daylight (Ali et al, 1977;Jacobsen et al, 2002). Also perch spawning takes place during daylight hours (Hergenrader, 1969).…”
Section: Introductionmentioning
confidence: 99%